1996
DOI: 10.1002/1529-0131(199608)9:4<292::aid-anr1790090414>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient education interventions in osteoarthritis and rheumatoid arthritis: A meta-analytic comparison with nonsteroidal antiinflammatory drug treatment

Abstract: Objective. To compare the effects of education interventions and nonsteroidal antiinflammatory drug (NSAID) treatment on pain and functional disability in patients with osteoarthritis (OA), and on pain, functional disability, and tender joint counts in patientswith rheumatoid arthritis (RA). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(107 citation statements)
references
References 39 publications
7
92
0
7
Order By: Relevance
“…As in the 2 previous meta-analyses of patient education programs (15,16), the effect sizes in our review, although statistically significant for most outcomes, were relatively small. In the face of these findings, the question arises, what, if any, is the clinical significance of these effects?…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As in the 2 previous meta-analyses of patient education programs (15,16), the effect sizes in our review, although statistically significant for most outcomes, were relatively small. In the face of these findings, the question arises, what, if any, is the clinical significance of these effects?…”
Section: Discussionsupporting
confidence: 61%
“…In the face of these findings, the question arises, what, if any, is the clinical significance of these effects? As noted earlier, Superio-Cabuslay et al (16) have suggested that the relatively small effect sizes they observed were clinically relevant because, in most instances, patients in these interventions were already receiving standard medical care and, therefore, any changes in outcome (e.g., pain, function, number of tender joints, psychological status) over and above what patients were receiving as a result of their usual care would be clinically important.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Sin embargo, se evidencia asociación entre referir haber sido informados sobre su artrosis y autorreporte de salud agrupado en dos bloques: uno insufi ciente (muy mal, mal, menos que regular) y otro al menos sufi ciente (regular, más que regular y bien), lo que confi rma lo seña-lado por diversas publicaciones 15,16 . Sería interesante observar, después de aplicar un programa de educación, los efectos sobre su funcionalidad o calidad de vida.…”
Section: Discussionunclassified
“…Entregando benefi cios adicionales a su tratamiento con antiinfl amatorios no esteroidales, mejora la percepción sobre el dolor y la funcionalidad 16 .…”
unclassified